Pre-Inoculation with Endophytic Bacteria for Improved Tolerance to Fusarium Wilt of Banana - Mohd Fishal, Elya Masya (2009)
Banana (Musa sapientum) is one of the important fruit crops cultivated in Malaysia and recognized as one of the important food sources in the tropics. Efforts are being undertaken to double the production figures in the next five or more years. The major constrain in banana cultivation is the occurrence of a serious disease problem that causes huge economic losses to the banana industry. Bananas are susceptible to Fusarium wilt caused by soil-borne Fusarium oxysporum f. sp. cubense (Foc). Since the control of Fusarium wilt is limited by the ineffectiveness of chemical and cultural methods and the lack of commercially suitable resistant cultivars, biological control by using endophytic bacteria could give the promising approach to control Fusarium wilt in banana. This study was undertaken with the aim to evaluate the effect of preinoculation with endophytic bacteria in the activation of defense related compounds to increase tolerance to Foc Race 4 (FocR4) in susceptible banana seedlings var Berangan. Endophytic bacteria (Pseudomonas aeruginosa (UPMP3) and Burkholderia cepacia (UPMB3)), isolated from healthy oil palm roots have strong antagonistic effect against FocR4, improving growth vigour and enhancing tolerance of susceptible banana seedlings to Fusarium wilt. In-vitro dual culture screening test showed percentage inhibition of radial growth (PIRG) of FocR4 with values of 63.47% for UPMP3 and 54.93% for UPMB3, respectively. Inhibitory metabolites produced in culture by UPMB3 and UPMP3 singly and as mixture (UPMP3+UPMB3) tested have also inhibitory effects on mycelia growth of FocR4 at 65%, 80% and 79.5% respectively. Pre-inoculation with UPMB3 and UPMP3 singly and as mixture to tissue-culture banana seedlings var Berangan triggered the production of defense related compounds; peroxidase, phenylalanine ammonia lyase, lignithioglycolic acid and PRproteins (chitinase and β-1, 3-glucanase). Induction of the defense related compounds enhanced lignifications which could be responsible for increase rigidity and strengthening of cell walls, acting as physical barriers to infection. PR-protein (chitinase and β-1, 3-glucanase) were able to degrade fungal cell walls and inhibit the spread of FocR4 in the host tissues. Development of Fusarium wilt was slow in seedlings pre-inoculated with endophytic bacteria and challenged inoculated with FocR4. The area under the disease progress curve (AUDPC) as a measure of the disease progress in UPMP3 preinoculated seedlings was 1300.12 units2 as compared to control at 2368.76 units2. The rate of disease progress was 0.08 unit day-1. Vegetative growth based on measurements of increase in height and pseudostem diameter, total number of leaves and chlorophyll content was also significantly enhanced in UPMP3 pre-inoculated seedlings. Bio-efficacy testing in glasshouse trial confirmed that pre-inoculation with UPMP3 as a promising biocontrol inducer in the activation of host defense systems and increasing tolerance to FocR4 infection in susceptible tissue-culture banana var Berangan.